Frequency of occurrence of genetic polymorphisms associated with sports success in elite athletes in team sports - E. Yu. Sorokina; N. N. Denisova; E. E. Keshabyants (National Electronic Information Consortium (NEICON), 2021)
Objective: to evaluate the frequency of occurrence of polymorphisms rs1815739 (ACTN3 gene), rs2016520 (PPARD gene), rs1042713 (ADRB2 gene), rs1799945 (HFE gene) in athletes of highperformance sports.Materials and methods: genotyping was performed using allelespecific amplification with realtime detection of the results and using TaqMan probes.Results: a higher frequency of alleles associated with endurance was found: the t allele of the rs1815739 polymorphism (ACTN3 gene), the g allele of the rs2016520 polymorphism (PPARD gene), the g allele of the rs1042713 polymorphism (ADRB2 gene), and the g allele of the rs1799945 polymorphism (HFE gene) in athletes of game sports.Conclusion: the results of genotyping of polymorphisms associated with endurance in the examined athletes showed a higher frequency of occurrence than in the population as a whole.